Progressive improvement in short‐, medium‐ and long‐term graft survival in kidney transplantation patients in Ireland – a retrospective study. (14th August 2019) - Sexton, Donal J.; O'Kelly, Patrick; Williams, Yvonne; Plant, William D.; Keogan, Marie; Khalib, Khairin; Doyle, Brendan; Dorman, Anthony; Süsal, Caner; Unterrainer, Christian; Forde, James; Power, Richard; et al.
Summary: It is often quoted that while short‐term graft survival in kidney transplantation has improved in recent years, it has not translated into a commensurate improvement in long‐term graft survival. We considered whether this was true of the entire experience of the national kidney transplant program in Ireland. A retrospective analysis of the National Kidney Transplant Service (NKTS) database was undertaken to investigate patient and graft survival for all adult first deceased donor kidney transplant recipients in Ireland, 1971–2015. Three thousand two hundred and sixty recipients were included in this study. Kaplan–Meier methods were used to estimate survival at each time period post transplant for the various eras of transplantation. Uncensored graft survival has improved over the course of the program in Ireland at various time points despite risk factors for graft failure progressively increasing over successive eras. For example the graft survival at 15 years post transplant has increased from 10% in 1971–1975 to 45% by 1996–2000. Ireland has experienced a progressive improvement in long‐term graft survival following kidney transplantation. Whether these trends are attributable to biological or nonbiological factors is unclear but likely involves a combination of both.